CORRELATION BETWEEN INTELLECTUAL PROPERTY AND SCIENTIFIC ACTIVITY - Shust, Nataliia (Proceedings of National Aviation University (archive), 2017)
Purpose: The article is dedicated to the analysis of legal nature and peculiarities of optimal correlation between the notions of intellectual property and scientific activity. Nowadays intellectual property as institution goes through the period of establishment in Ukraine. As the Soviet system of civil law was based on recognition and regulation of authors’ rights for the authors of scientific works, discoveries, inventions and innovation proposals as the ones having mainly relative, i.e. legally mandatory, but not absolute character. Getting started to define the notion of intellectual property and intellectual property right in the system of interaction with scientific activity, it is important to say that such notion as “intellectual property” still needs enhancement. Its imperfection is due to the fact that this kind of property implies being formed by intellectual efforts of the author of scientific work, but legally it is processed with the help of documents that guarantee property right. Methods. General scientific method, philosophical method, specially-legal method of scientific research, system analysis method. Results: It is important to emphasize that not every result of scientific or creative work can become the object of intellectual property right, but the one that corresponds with law. Any scientific work falls within the purview of law if it corresponds with law demands. Scientific and technical results obtain legal protection only in case of appropriate qualification established by specific agency of State administration and issuement of law-enforcement document being limited by the territory of Ukraine. Protection of rights on the territory of other countries is realized only on the basis of correspondent international conventions and treaties. Discussion: Advanced modern countries realized the meaning and importance of usage and proper protection of creative and scientific work results known as “intellectual property” in accordance with fast pace of social and industrial development long time ago. Legal nature and peculiarities of optimal correlation between the notions of intellectual property and scientific activity is an important topic for the future research.